An Assessment of Different Clinical Presentations in Cases of Colorectal Cancer - Muhammad Alim, Bahadur Khan, Abdul Latif, Khaleel Ahmad Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To assess the different clinical presentations in cases of colorectal cancer. Material and methods: Between April 2021 to October 2021 total 90 diagnosed patients of colorectal cancer confirmed on histopathology, either male or female having age 25-75 years were selected from Department of Surgery, Loralai Medical College Loralai. Different clinical presentations of colorectal cancer were assessed. Results: In present study age range was 25-75 years with mean age 48.58 ± 15.16 years. Grade-I cancer was found in 24 (27%) patients followed by grade-II cancer in 29 (32%) patients and grade-III cancer in 37 (41%) patients. Regarding clinical presentation of patients, bleeding per rectum was found in 73 (81.1%) patients followed by altered bowel habits in 67 (74.4%) patients, anemia in 27 (30%) patients and weight loss was seen in 19 (21.1%) patients. Conclusion: Results of present study showed that most of the patients had grade-III colorectal cancer. Males were prominent as compared to females. Most common presenting symptom was bleeding per rectum. Family history of cancer and obesity have no association with presenting symptoms.